Chemical and Physical Behavior of Rubberized Concrete: A Review - Musarat, M.A. (Institute of Electrical and Electronics Engineers Inc., 2021)
Concrete is susceptible to chemical attack and temperature changes, especially when exposed to extreme heat, which raises the internal pore water pressure. When used as a fine aggregate replacement in concrete, crumb rubber can help to avoid spalling by allowing the pore water pressure to escape when the temperature is high. However, research shows that when rubberized concrete is compared to ordinary concrete, its fresh properties degrade. To overcome the problem caused by material composition change, nanomaterials have been introduced as enhancing admixture. Concrete elements are exposed to a harsh environment such as acidic conditions. Hardened cementitious matrix undergoes deterioration when being attacked by different acids and various concentrations. When acids are being encountered with a cement-based matrix, the high solubility of salts is produced and induces a high amount of porosity, eventually producing shorter service life and increased expenditures. Â© 2021 IEEE.